HISTOLOGICAL EVIDANCES FOR DE NOVO SHOOT FORMATION IN AN ENDANGERED MEDICINAL HERB- CURCULIGO ORCHIOIDES GAERTN - OSHNI P. ADIYECHA; YOGESH T. JASRAI (The Bioscan, 2011)
In vitro derived leaf explants of Curculigo orchioides Gaertn. were cultured on MS media containing half- strength nitrogen salts and 0.44 μM BA. The histological events leading to de novo shoot formation were evaluated. The studies clearly demonstrated initiation of the shoot buds from the phloem parenchyma cells on 9th day of culture initiation. The present work focuses on the sequence of events leading to the shoot organogenesis of Kali musli.